ANALISIS KEMAMPUAN BERPIKIR GEOMETRI SISWA SMP BERBASIS TEORI VAN HIELE DITINJAU DARI GENDER - Muhammad Fikri (Jurnal Edukasi dan Penelitian Matematika, 2023)
Geometry is an important material in the mid secondary school curriculum which is still relatively low in performance because pupils still have trouble learning geometry. This study aims to describe the geometrical thinking ability of mid high school pupils based on Van Hiele's thinking stages in terms of gender. This study use descriptive research using a qualitative approach. The research subjects are pupils of class IX.1 at SMP Negeri 1 Lareh Sago Halaban selected by using purposive sampling. Research data were collected through written test and interviews. That test in the form of geometrical ability test of triangle and quadrilateral material and free unstructured interviews. Data analysis techniques using the Miles and Huberman model, namely activities carried out simultaneously: data reduction, data presentation, and drawing conclusion or verification. The results revealed that: (1) the ability to think geometry in junior high school pupils diverse each stage of geometry thinking. (2) Geometry thinking ability of pupils in class IX.1 SMP N 1 Lareh Sago Halaban is 26.92% are at the Pre-visualization stage , 15.38% are at the visualization stage (level 0), 19.24% are at the analysis stage (level 1), there are no pupils who reach stage 2 (informal deduction), and there are 38.46% pupils can not be determined based on Van Hiele's geometry thinking stages. (3) There is no significant differences between of male pupils and female pupils at the geometry thinking ability.Keywords– Thinking stage, Geometrical thinking,. Van Hiele Theory, Triangle and quadrilateral.